Virginia Woolf and the politics of language - Allen, Judith (Virginia Woolf scholar) (Edinburgh University Press, 2010)
Through close readings of Woolf's essays, including 'Montaigne', A Room of One's Own, 'Craftsmanship', Three Guineas and 'Thoughts on Peace in an Air Raid', Allen shows how Woolf's politics are expressed and enacted in her writing. She then works from a wide range of sources to relate Woolf's views and methods to our current political situation. These sources range from Michel de Montaigne to the Dixie Chicks, from the Northcliffe Press newspaper empire of World War I to today's mainstream newspapers, Rupert Murdoch's empire, satirical news shows like The Colbert Report and The Daily Show and social media and the blogosphere.